Pengaruh Social Influence dan Live Streaming Terhadap Keputusan Pembelian Melalui Customer Engagement: Studi pada Produk Glad2glow - Juliyanti Juliyanti; Rizky Fauzan; Erna Listiana; Nur Afifah; Harry Setiawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research aims to analyze the influence of Live streaming and social influence on the purchase decision of imported skincare products through customer engagement mediation on e-commerce platforms in Indonesia. The research was conducted in Indonesia in November - January 2026. This research is a quantitative study with purposive sampling of 165 consumers of Glad2Glow products who actively follow live streaming. Data was analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results show that Customer engagement has a significant positive effect on purchasing decisions. Live streaming has a significant positive effect both directly on purchasing decisions and indirectly through customer engagement. Social influence has a significant positive effect both directly on purchasing decisions and indirectly through customer engagement. This finding confirms the S-O-R model in live streaming, confirming the crucial role of digital interaction and social validation in building consumer engagement that drives purchase conversion. This research is expected to be able to provide theoretical and practical contributions to digital marketing strategies in the Indonesian collectivistic market.